Dysphagia predicts poor outcome in late-stage Parkinson's disease - Fabbri, Margherita (2019)
"BACKGROUND: Few data exist on the rate of clinical progression for Parkinson's disease (PD) patients who have entered a late stage of the disease. OBJECTIVE: Study the clinical progression of a late-stage PD (LSPD) population over one year follow-up. METHODS: 50 LSPD patients (Schwab and England ADL Scale <50 or Hoehn Yahr Stage >3 in MED ON) underwent an extensive clinical assessment at baseline and after one year and an acute levodopa test at baseline. RESULTS: Mean age of LSPD patients (female 46%) was 77.5 ± 5.9 years and mean disease duration was 15.5 ± 6.5 years. At baseline, 76% had levodopa-induced motor complications (MC), usually non-troublesome, 68% were demented, 54% had psychosis and 68% depression. Caregiver distress was high. l-dopa responsiveness was mild (18% ± 12 of improvement on MDS-UPDRS-III). After one-year, 20% of the patients were dead, institutionalized or HY 5. MDS-UPDRS-motor mean score worsened 7.2 ± 10.3 points although there was heterogeneity between patients, and there was a global worsening of non-motor symptoms, mostly in cognition/mood, urinary and gastrointestinal domains. Nevertheless, MC improved despite similar levodopa equivalent dose. Functional independence and quality of life worsened. Dysphagia severity at baseline predicted a poor outcome (death, institutionalization or HY 5) (Hazard ratio 2.3, 95% CI 1.12-4.4; p = 0.01), whereas magnitude of l-dopa response of LSPD patients did not. CONCLUSIONS: LSPD patients still present a significant, although heterogeneous, motor and non-motor progression over 1 year. Dysphagia severity predicts the occurrence of additional disease severity milestones and its management must be prioritized."